2020
DOI: 10.14202/vetworld.2020.1457-1461
|View full text |Cite
|
Sign up to set email alerts
|

Malacca leaf ethanolic extract (Phyllanthus emblica) as a hepatoprotector of the liver of mice (Mus musculus) infected with Plasmodium berghei

Abstract: Background and Aim: Although existing research confirms the antiparasitic effect of the Malacca plant against Plasmodium, its effect on the liver, one of the target organs of Plasmodium has not been investigated. Therefore, this study was conducted to explore the potential of the ethanolic extract of Malacca (Phyllanthus emblica) leaves in preventing liver damage in mice (Mus musculus) caused by Plasmodium berghei infection. Materials and Methods: This study was conducted using the livers of 18 mice fixed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The appearance of hepatocyte necrosis is highly dependent on sporozoite infection Plasmodium. This is the same as previous research which states that Plasmodium can cause hepatocyte necrosis (Asmilia et al, 2020).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 88%
“…The appearance of hepatocyte necrosis is highly dependent on sporozoite infection Plasmodium. This is the same as previous research which states that Plasmodium can cause hepatocyte necrosis (Asmilia et al, 2020).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 88%
“…In the model used for this study, hemozoin, a free heme derived from high parasitemia and hemolysis, was likely to contribute to the oxidative stress response in the liver [ 29 ]. Another study demonstrated that PbANKA infection caused hydropic degeneration, and continuous degeneration can cause liver cell necrosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PbANKA infection in mice is a well-known model of malaria-induced acute kidney injury [ 30 ]. Here, PbANKA-infected mice showed kidney injury as confirmed through manifestations of significantly increased BUN and creatinine levels in the untreated group, consistent with previous reports [ 38 ].…”
Section: Discussionmentioning
confidence: 99%